HOW TO CREATE NEW LANGUAGE LEARNING HABITS IN YOUTH. (Journal of Universal Science Research, 2023)
Today, it is very important for everyone to know foreign languages. The world becoming increasingly globalized and bilingual is not just hotness is becoming the need of the hour. How to learn foreign languages with others a life focused on learning to truly communicate and connect with them skill. Why should we learn foreign languages? Why am I learning foreign languages now? I will write about the reasons why it is necessary to study